(untitled) (Research, Society and Development, 2020)
Assistance, reception and humanization is essential in building a trusting relationship between pregnant women and women who have recently given birth to the health team. The general objective was to evaluate nursing care and reception at a public maternity hospital. Exploratory-descriptive research, with a qualitative approach, carried out in a public maternity hospital in the city of Caxias, Maranhão. Sample composed of 15 pregnant women and puerperal women, the data were obtained from semi-structured interviews with open questions, the collected information was submitted to content analysis, a technique proposed by Bardin. The reports show that there was satisfaction of some of the patients in relation to nursing care and reception at the aforementioned public maternity, however, most reported dissatisfaction because they took into account all the care provided from admission to discharge. A relevant data was the reference that the patients made regarding the lack of communication from the health team during the performance of procedures, where the team chose not to consult or inform the patients during the performance of procedures. It was concluded that embracement and nursing care was unsatisfactory, even if pregnant women enter the maternity hospital, the subsequent assistance suffers a deficit in quality, some of the pregnant women and the puerperal women refer to the instability of nursing professionals, considering that some are presumptuous and rude in providing assistance, which is considered obstetric violence.